Graphic 3D ergonomic database in evaluation of virtual models of kitchen design/adaptation for needs of handicapped persons - Branowski, B.; Rychlik, M.; Sydor, M.; Zabłocki, M. (Видавництво Львівської політехніки, 2011)
The paper presents a concept for the utilisation of anthropometric and biomechanical graphic 3D database of a motorically handicapped person using a wheelchair for purposes of analysis and assessment of kitchen space design. Contemporary tendencies in kitchen design or adaptation for disabled persons or senior citizens were discussed. Methodological assumptions as well as a test station for measurements of reach of arms and forces for a male disabled person sitting in a wheelchair were presented. The obtained results were arranged developing a virtual model of interactions between a handicapped user and kitchen equipment. Using the elaborated model, the field of vision and accessibility to a heating plate and cabinets in a standard and adapted kitchen were analysed. In conclusions, issues associated with kitchen adaptation were allocated into groups. Usefulness of the described database to perform digital simulations of various systems of technical facilities was emphasised. This approach allows appropriate arrangement of kitchen space in a way that takes into consideration unrealised needs of users.
Keywords: kitchen adaptation; disabled person; ergonomic database